From discrimination to growth? Student stress in the association between perceived discrimination and posttraumatic growth among African international students in South Africa - Juliette Bih Nkarenbi; Erhabor S. Idemudia; Lawrence Ejike Ugwu (PLoS ONE, 2026)
Background International students relocating across borders often face perceived discrimination, a form of cumulative adversity that may undermine well-being and may also be relevant to growth-related outcomes. Little is known about how perceived discrimination is associated with posttraumatic growth (PTG), and whether student stress helps explain that association, among African international students in South Africa. Methods We surveyed 781 non-South African students aged 18–49 (54% men, 46% women) enrolled at four public universities across Gauteng, North West, Western Cape, and Free State. Perceived discrimination was assessed with the relevant subscale of the Acculturative Stress Scale for International Students; student stress was measured with four subscales (academic, interpersonal, physical and environmental) of the Student Stress Inventory; and PTG was measured with five subscales (personal strength, new possibilities, improved relationships, spiritual growth and appreciation of life) of the Posttraumatic Growth Inventory. Parallel multiple-mediator models and quadratic regression were used to estimate indirect associations and nonlinear patterns, adjusting for age and gender. Results Perceived discrimination was moderately and positively associated with all student stress domains. It was not directly associated with most PTG facets, except for a small positive association with personal strength. Total indirect associations through student stress were nonsignificant; however, specific indirect paths diverged. Interpersonal stress showed positive indirect associations with improved relationships, new possibilities, and personal strength, whereas academic and environmental stress showed negative indirect associations with several PTG facets. Small positive quadratic terms indicated U-shaped associations between perceived discrimination and improved relationships, new possibilities, and personal strength, with the lowest estimated PTG values occurring at modestly low levels of discrimination. Conclusions Perceived discrimination was associated with PTG through distinct student-stress patterns. Academic and environmental stress showed negative associations with several PTG facets, whereas interpersonal stress showed positive associations with some PTG facets. These findings should not be interpreted as suggesting that discrimination is beneficial; rather, they indicate heterogeneous responses to adversity. Interventions should prioritise reducing discrimination and related stressors while strengthening supportive resources for international students in South Africa.